Modernization problems of the Juvenile Justice System of the Republic of Kazakhstan - Bogatyreva, L.B.; Taitorina, B.A.; Abdukarimova, Z.T. (Bulletin of the Karaganda University “Law Series”, 2019)
The article concerning the problems of modernizing the existing structure of Juvenile Justice in order to ex-pand their powers, taking into account the guarantees and obligations of the Government, as well as giving each of the authorities an independent legal status in order to ensure the best interests and rights of Child. The authors specify the task of developing new approaches in determining the directions of further development of the system of Juvenile authorities. The proper level of its elemental composition is important for the effec-tiveness of juvenile justice: the Juvenile Courts, the Juvenile Police, the Juvenile Prosecutor’s Office, Social Services, the Juvenile Advocacy. It should be noted that in the Republic of Kazakhstan these services are dif-ferent from the similar services in foreign countries inall aspects. Updating the problem of bringing the na-tional legislation of the Republic of Kazakhstan in accordance with international standards. Suggest to im-plement the new Juvenile Legislation package, create a full-fledged complex of specialized Juvenile Justice authorities. Substantiate the necessity of taking measures on forming the sufficient budget for the reorganiza-tion and financing the activities of all system authorities. Also involve non-governmental investments in Government programs and projects on the social rehabilitation of minors. The authors are modeling a qualita-tively new unified Juvenile Justice System focusing on the weakest link of this system — Social Service In-stitutions.